Computer-aided design of polymer-matrix composite structures - Hoa, S. V. (Suong V.) (Mechanical engineering (Marcel Dekker, Inc.), 1995)
Reviews the computer-aided technology and manufacturing techniques utilized in the design of structures made of polymer-matrix composite materials. This work details available microcomputer programs based on laminate theory and well-established principles for the prediciton of properties of composite materials.